POLA PERTUMBUHAN KAPANG Monascus purpureus PADA MEDIA BERAS, JAGUNG, DAN KOMBINASI BERAS - JAGUNG - Retnowati, Yuliana; Abdurrahmat, Asep S.; Kumaji, Syam; Umadji, Nurinda (Jurnal Entropi, 2009)
The aim of the study was to determine the pattern of Monascus purpureus growth on the rice, corn, and rice-corn combination medium. The study was done at microbiology laboratory of Biologi Departement, Gorontalo State University. The study was based on descriptive methods that describe the pattern of Monascus purpureus growth on rice, corn and rice-corn combination medium. The changes of mycelium colour and the addition of mycelium pigmentation area on 0-16 days observations as the indikator of fungal growth. The results showed that the ability of Monascus purpureus to grow at rice, corn,and rice-corn combination medium was different. The difference was showed on the adaptation time or lag grouth phase at each of the growth medium. The stationary growth phase of Monascus purpureus was reached at fifth days after adaptation periode. The pigment production of Monascus purpureus was different at each of growth medium, while 75 %, 95 %, 100 % at rice, corn, and ricecorn combination medium.